Enhancing Tourists' Satisfaction: Leveraging Artificial Intelligence in the Tourism Sector - Ma, Siyao (Pacific International Journal, 2024)
The tourism industry plays a pivotal role in global economic growth and development, significantly contributing to GDP, job creation, and cultural exchange. However, delivering exceptional tourist experiences remains challenging due to factors such as overcrowding, inadequate infrastructure, language barriers, and cultural insensitivity. The integration of artificial intelligence (AI) technologies offers a promising solution to these challenges. AI can enhance personalization, streamline operations, and improve resource allocation, thereby elevating the overall quality of the tourist experience. AI-driven technologies, such as machine learning algorithms, virtual assistants, augmented reality (AR), and virtual reality (VR) applications, can provide tailored recommendations, multilingual support, and immersive experiences. Moreover, AI can enhance safety and security through predictive analytics and real-time monitoring. While the potential of AI to revolutionize the tourism industry is immense, responsible and ethical implementation is crucial to ensure that these innovations benefit all stakeholders and mitigate potential risks. Embracing transparency, privacy, and fairness in AI practices will foster trust and create more inclusive, sustainable, and enriching travel experiences globally.